PENGARUH PEMBERIAN BOKASI LEGUMENOSE DAN PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL SAWI PADA TANAH ALUVIAL - Sanga Tariu, Are Pabayo; Asnawati, Asnawati; Maulidi, Maulidi (Jurnal Sains Pertanian Equator, 2022)
ABSTRACTThis study aimed to obtain the best interaction dose of bokasi legume and NPK fertilizer on the growth and yield of mustard greens on alluvial soil. This research started from 28 April "“ 28 May 2022, on Jl. Perdamian, Parit Banjar, Melati Hamlet, Kalimas Village, Sungai Kakap District, Kubu Raya Regency. The study used a factorial design with a Completely Randomized Design (CRD) pattern consisting of 2 treatment level factors. and the second factor is the dose of NPK fertilizer in which each factor consists of 3 levels. Each treatment was repeated 3 times and the treatment unit contained 4 plant samples. The treatment in question is the first factor, the dose of bokasi legumes b1 = 20 tons/ha, b2 = 30 tons/ha, b3 = 40 tons/ha, and the second factor is the dose of NPK fertilizer consisting of 3 levels, namely n1 = 50 kg/ha, n2 = 100 kg/ha, n3 = 150 kg/ha. The variables observed in this study were the number of leaves, leaf area, root volume, fresh weight and dry weight. Based on the results of the study, it can be concluded that the provision of 30 tons/ha of legumenose bocation + 50 kg/ha of NPK fertilizer is an interaction that provides the most effective growth of mustard greensKeywords : alluvial soil, bokasi legumes, mustard greens, legume plant, NPK